Algirdo Jeronimo Landsbergio archyvas Kaune - Vedrickaitė, Imelda (Colloquia, 2015)
Virginija Babonaitė-Paplauskienė, Kelionė į Algirdo Landsbergio kelionę: Archyvai, Kaunas: Naujasis lankas, 2014, ISBN 978-9955-03-871-9
Keywords: -